Expression of sodium-dependent dicarboxylate transporter 1 (NaDC1/SLC13A2) in normal and neoplastic human kidney - Lee, Hyun-Wook (Am J Physiol Renal Physiol, 2017)
Regulated dicarboxylate transport is critical for acid-base homeostasis, prevention of calcium nephrolithiasis, regulation of collecting duct sodium chloride transport, and the regulation of blood pressure. Although luminal dicarboxylate reabsorption via NaDC1 (SLC13A2) is believed to be the primary mechanism regulating renal dicarboxylate transport, the specific localization of NaDC1 in the human kidney is currently unknown. This study’s purpose was to determine NaDC1's expression in normal and neoplastic human kidneys. Immunoblot analysis demonstrated NaDC1 expression with an apparent molecular weight of ~61 kDa. Immunohistochemistry showed apical NaDC1 immunolabel in the proximal tubule of normal human kidney tissue; well-preserved proximal tubule brush border was clearly labeled. Apical NaDC1 expression was evident throughout the entire proximal tubule, including the initial proximal convoluted tubule, as identified by origination from the glomerular tuft, and extending through the terminal of the proximal tubule, the proximal straight tubule in the outer medulla. We confirmed proximal tubule localization by colocalization with the proximal tubule specific protein, NBCe1. NaDC1 immunolabel was not detected other than in the proximal tubule. In addition, NaDC1 immunolabel was not detected in tumors of presumed proximal tubule origin, clear cell and papillary renal cell carcinoma, or in tumors of nonproximal tubule origin, oncocytoma and chromophobe carcinoma. In summary, 1) in the human kidney, apical NaDC1 immunolabel is present throughout the entire proximal tubule, and is not detectable in other renal cells; and 2) NaDC1 immunolabel is not present in renal tumors. These studies provide important information regarding NaDC1’s role in human dicarboxylate metabolism.